2018
DOI: 10.1097/mph.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Cerebral Sinovenous Thrombosis Associated With l-Asparaginase In Children With Acute Lymphoblastic Leukemia: A Single Institution Experience Over 17 Years

Abstract: Incidence of symptomatic L-asparaginase associated CSVT during ALL treatment was 1.5% with high case fatality rate (28%). It is noteworthy that full neurological recovery is likely in surviving patients, and rechallenge with L-asparaginase is safe with heparin prophylaxis. Currently available screening methods are not practically implementable in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The overall mortality rate in ALL patients as a result of VTE varies between 0% and 4.8% . A substantial proportion of VTE in ALL is due to cerebral venous sinus thrombosis (CVST) with a reported mortality between 0% and 28% . Morbidity includes recurrent thrombosis, neurologic changes, catheter removal, bleeding due to antithrombotic agents, and the development of the postthrombotic syndrome .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mortality rate in ALL patients as a result of VTE varies between 0% and 4.8% . A substantial proportion of VTE in ALL is due to cerebral venous sinus thrombosis (CVST) with a reported mortality between 0% and 28% . Morbidity includes recurrent thrombosis, neurologic changes, catheter removal, bleeding due to antithrombotic agents, and the development of the postthrombotic syndrome .…”
Section: Introductionmentioning
confidence: 99%
“…6 A substantial proportion of VTE in ALL is due to cerebral venous sinus thrombosis (CVST) with a reported mortality between 0% and 28%. [8][9][10][11] Morbidity includes recurrent thrombosis, neurologic changes, catheter removal, bleeding due to antithrombotic agents, and the development of the postthrombotic syndrome. [12][13][14]15 Furthermore, VTE can lead to suboptimal ALL therapy, due to the necessity to interrupt, delay, or even discontinue chemotherapy, and thereby to inferior disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ALL may develop thrombi in different parts of the body. 3 CVST is a rare complication of ALL, which may lead to death, 10 and the clinical symptom are nausea, vomiting, headache, seizures, lethargy, and altered consciousness. 11 CVST can also be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…4 30 In 25% of the cases, VTE occurred as a CSVT, a potentially severe complication, with a high case-fatality rate of 0 to 29%. 31 32 33 The incidence of CSVT in ALL patients is considerably higher compared with the normal pediatric population. 33 Previous studies have shown that patients during ALL treatment are at an increased risk for CSVT.…”
Section: Discussionmentioning
confidence: 99%
“…32 33 35 As in the study by Abbott et al, the current study did not seem to show beneficial effect of FFP for the prevention of CSVT. 31…”
Section: Discussionmentioning
confidence: 99%